Combining short-term response and long-term vision: Rethinking the approach to fertilizer subsidies - Ayalew, Hailemariam; Breisinger, Clemens; Karugia, Joseph T.; Kimaiyo, Faith Chepkemoi; Kimathi, Sally; Olwande, John; Abay, Kibrom A.; Rasche, Frank; Wanjiru, Lilian; Muchigiri, Simon; Owoko, Peter (CGIAR, 2024)
The presentation slides were used by speakers during the "Combining Short-Term Response and Long-Term Vision: Rethinking the Approach to Fertilizer Subsidies" event held on March 20, 2024, in Nairobi, Kenya. The event was hosted by hosted by Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH, International Food Policy Research Institute (IFPRI), and the CGIAR Research Initiatives on National Policies and Strategies (NPS) and Excellence in Agronomy (EiA) in partnership with the Kenya Ministry of Agriculture and Livestock Development.